In vitro multiplication and phytochemical evaluation of Apios americana Medik for enhanced production of the staple food and tissues with versatile bioactivities. - Okello, Denis; Gang, Roggers; Rahmat, Endang; Yang, Sungyu; Ban, Yeongjun; Chung, Yuseong; Lee, Jun; Kang, Youngmin (Kabale University, 2024)
Apios americana Medik tissues, including tubers, flowers, leaves, and vines have both nutritional and therapeutic benefits. These tissues are extensively used in products like beverages and food supplements, driving an exponential increase in worldwide demand for the plant. However, conventional propagation of A. Americana through seeds and tubers faces several challenges, including limited seed sets under manual pollination, resulting in reduced production. To overcome these challenges, micropropagation emerges as a promising solution. The current research study has developed an effective in vitro propagation strategy for A. americana using direct regeneration from apical segment explants. Full-strength Quoirin and Lepoivre (QL) medium, supplemented with vitamins and 2.0 mg/L benzylaminopurine (BAP), yielded the highest number of shoots (7.50 ± 0.06) per apical segment explant. QL medium fortified with 1.0 mg/L indole-3-butyric acid (IBA) demonstrated the highest root number (2.80 ± 0.30), length (85.80 ± 7.49 mm), and surface area (10.40 ± 0.82 cm2) in regenerated A. American shoots. The survival rate of the regenerants in the ex-vitro environment was 92.7% after acclimatization. In vitro-regenerated A. Americana plants and mother plants exhibited similar ploidy levels, chlorophyll content, photosynthetic rate, phytochemical composition, and antioxidant capacity, indicating similarity in their physiological and biochemical properties. This protocol offers a rapid and scalable method for generating high-quality, A. Americana plant stocks with stable genome size/ploidy level, meeting the exponentially growing demand for plant tissues. Additionally, it holds potential applications in A. Americana breeding and germplasm preservation.